Out of poverty : sweatshops in the global economy - Powell, Benjamin, 1978- (Cambridge : Cambridge University Press, 2014)
This book provides a comprehensive defense of third-world sweatshops. It explains how these sweatshops provide the best available opportunity to workers and how they play an important role in the process of development that eventually leads to better wages and working conditions. Using economic theory, the author argues that much of what the anti-sweatshop movement has agitated for would actually harm the very workers they intend to help by creating less desirable alternatives and undermining the process of development. Nowhere does this book put'profits' or'economic efficiency' above people. Improving the welfare of poorer citizens of third world countries is the goal, and the book explores which methods best achieve that goal. Out of Poverty will help readers understand how activists and policy makers can help third world workers.
Preface -- Acknowledgements -- Introduction -- The anti-sweatshop movement -- The economics of sweatshop wage determination -- Don't cry for me Kathie Lee : how sweatshop wages compare to alternatives -- Health, safety, and working conditions laws -- Save the children? -- Is it ethical to buy sweatshop products? -- A history of sweatshops, 1780-2010 -- The process of economic development -- What good can activists do? -- Conclusion -- References -- About the author.
Title from publisher's bibliographic system (viewed on 08 Oct 2015).
Keywords: Sweatshops; Anti-sweatshop movement -- History; Economic development -- Moral and ethical aspects